Evaluation of different botanicals and non-target pesticides against Sclerotium rolfsii causing collar rot of lentil - S.S.L. SRIVASTAVA, R.K. PANDEY and P.K. GUPTA, SHEO RAJ SINGH*, R.K. PRAJAPATI (Indian Phytopathology, 2007)
Nine botanicals and eight non-target pesticides were evaluated in-vitro against Sclerotium rolfsii causing collar rot of lentil (Lens culinaris Medik). Among them leaf extract of marigold (Tegetes erecta) followed by neem extract (Azadirachta indica) caused maximum inhibition of mycelial growth and sclerotial production, its size and viability. Monocrotophos, 2, 4-0 and Nuvan completely inhibited the mycelial growth and sclerotial production of the pathogen. Next effective pesticides may be utilized in future for the management of the disease caused by S. rolfsii.